HSP27 Protects Skin From Ultraviolet B -Induced Photodamage by Regulating Autophagy and Reactive Oxygen Species Production - Wang, Zi-Yue; Li, Ang; Huang, Xin; Bai, Gen-Long; Jiang, Yu-Xin; Li, Ruo-Lin; Liu, Chuan; Wen, Zhu-Yuan; Wang, Ping; Chen, Ai-Jun (Frontiers in Cell and Developmental Biology, 2022)
Ultraviolet (UV) irradiation has been well documented to be linked with almost all skin problems we know, and both dermis and epidermis may be affected to varying degrees by UV irradiation. Every time when exposed to sunlight without protection, our skin will step closer to photoaging, leading to irreversible consequences ultimately. Heat shock protein 27 (HSP27) is a vital protein involved in cell growth, autophagy, apoptosis, drug resistance, tumor genesis and metastasis. Evidence suggests that the organism is subjected to various internal and external environmental stresses (heat, oxidative stress, organic toxicants, etc.), and HSP27 with high expression has protective function. However, the expression of HSP27 in coping with UV irradiation have not been examined thoroughly. In this study, photodamage models were developed through different doses of UVB irradiation in human epidermal keratinocytes (HEKs) (30 mJ/cm2), human dermal fibroblasts (HDFs) (150 mJ/cm2) and mouse skin (2,700 mJ/cm2). HSP27 knockdown decreased cell viability and increased the incidence of UVB-induced reactive oxygen species (ROS) production. We got consistent results in vivo and vitro. Compared with that in the UVB group, the expression of LC3B was significantly lower, while the expression of p62 was significantly higher in the UVB + si-HSP27 group. It was also revealed that HSP27 knockdown reduced the expressions of some antioxidants, such as superoxide dismutase (SOD) and catalase (CAT), which accelerated UVB-induced ROS release. Moreover, histological results showed that epidermis was thickened and collagen fibers were disorganized in the UVB + si-HSP27 group. These findings have demonstrated that HSP27 might play a photoprotective role in the UVB-induced skin damage process by maintaining the normal autophagy and antioxidant level. It is implied that HSP27 could be a potential therapeutic target of photodamage. However, determination of the definitive mechanism requires further exploration.